LncRNA FGD5‐AS1 enhances the proliferation and stemness of hepatocellular carcinoma cells through targeting miR‐223 and regulating the expression of ECT2 and FAT1. Issue 7 (11th May 2022) - He, Chen‐Kun; Li, Zeng‐Bo; Yi, Da; Zhu, Xiang‐Ya; Liu, Rong‐Rong; Zhang, Dong‐Xin; Cao, Qian; Chen, Yi‐Ping
Abstract: Aim: Hepatocellular carcinoma (HCC) is common and causes many deaths worldwide. The aim of this study is to explore the mechanism by which long non‐coding RNA FGD5‐AS1 regulates HCC cell proliferation and stemness. Methods: Tumor and normal adjacent tissues were harvested from HCC patients. Real‐time quantitative reverse transcription‐PCR was applied to examine the expression of FGD5‐AS1, miR‐223, Epithelial cell transforming sequence 2 (ECT2) and FAT1. The protein levels of ECT2, FAT1, proliferating cell nuclear antigen (PCNA), OCT4, CD133 and CD90 were analyzed by western blot. The localization of FGD5‐AS1 was examined by Fluorescence in situ hybridization. Cell proliferation was analyzed with CCK‐8 and colony formation assays. Spheroid formation was used for analyzing cell stemness. Gene interaction was examined by RNA immunoprecipitation and luciferase activity assays. A subcutaneous xenograft mouse model was established to analyze HCC growth and stemness in vivo. Immunohistochemistry staining was used to analyze the expression PCNA and OCT4 in subcutaneous tumors. Results: FGD5‐AS1 was upregulated in HCC and its high expression indicated poor prognosis of patients. High expression of FGD5‐AS1 enhanced HCC cell proliferation and stemness. Knockdown of FGD5‐AS1 restrained tumor growth and stemness in mice. FGD5‐AS1 directly sponged miR‐223 and promoted the expression of ECT2 and FAT1 in HCC. Both knockdown of miR‐223 and overexpression of ECT2 and FAT1 reversed FGD5‐AS1 silencing‐mediated suppression of HCC cell proliferation and stemness. Conclusion: FGD5‐AS1 directly sponged miR‐223 and promoted the expression of ECT2 and FAT1 in HCC, thus enhancing HCC cell proliferation and stemness. Our study identifies potential prognostic biomarkers and therapeutic targets for HCC.